2007
DOI: 10.1562/0031-8655(2002)0760073ceimah2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 Expression in Murine and Human Nonmelanoma Skin Cancers: Implications for Therapeutic Approaches¶

Abstract: Inflammatory stimuli result in the production of cutaneous eicosanoids, which are known to contribute to the process of tumor promotion. Cyclooxygenase (COX), the rate‐limiting enzyme for the production of prostaglandins (PG) from arachidonic acid, exists in at least two isoforms, COX‐1 and COX‐2. COX‐1 is constitutively expressed in most tissues and plays various physiological roles, whereas increased COX‐2 expression is known to occur in several types of epithelial neoplasms. Enhanced PG synthesis is a poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 50 publications
4
87
0
1
Order By: Relevance
“…108 UVB-induced increase in cyclooxygenase-2 expression was abrogated both in murine and human nonmelanoma skin cancer models by topical application of GTPs. 108 Topical treatment of GTPs to mouse skin before UV exposure decreased UV-induced myeloperoxidase activity and number of infiltrating inflammatory leukocytes in the skin. 23, 109 Studies from our laboratory showed that topical application of GTPs before UV irradiation on the backs of human individuals resulted in significantly reduced erythema development as compared to those individuals who did not receive GTPs treatment.…”
Section: Tea/green Teamentioning
confidence: 99%
“…108 UVB-induced increase in cyclooxygenase-2 expression was abrogated both in murine and human nonmelanoma skin cancer models by topical application of GTPs. 108 Topical treatment of GTPs to mouse skin before UV exposure decreased UV-induced myeloperoxidase activity and number of infiltrating inflammatory leukocytes in the skin. 23, 109 Studies from our laboratory showed that topical application of GTPs before UV irradiation on the backs of human individuals resulted in significantly reduced erythema development as compared to those individuals who did not receive GTPs treatment.…”
Section: Tea/green Teamentioning
confidence: 99%
“…The inhibition of GJIC induced by hydrogen peroxide, but not TPA, is also blocked by treatment with EGCG [42,59]. Green tea extract and EGCG decrease the expression of COX-2 in chemical-or UV-induced carcinogenesis in rodents [2,5,43,54]. Tea polyphenols inhibit COX-dependent arachidonic acid metabolism by microsomes from normal colonic mucosa, with EGCG exhibiting the strongest inhibitory activity [32].…”
Section: Egcgmentioning
confidence: 99%
“…Tea polyphenols inhibit COX-dependent arachidonic acid metabolism by microsomes from normal colonic mucosa, with EGCG exhibiting the strongest inhibitory activity [32]. A transient elevation of COX-2 in mouse and human skin, on acute exposure to UVB, can be abrogated when the exposed area is pretreated with green tea extract [5]. A recent study showed that EGCG can suppress COX-2 expression induced by TPA in mouse skin in vivo and also in cultured human mammary epithelial cells, possibly by inhibiting the activation of both ERK and NF-κB [54].…”
Section: Egcgmentioning
confidence: 99%
“…48 Considering this, COX-2 inhibitors (Table 2), such as celecoxib, have been used in animal models to prevent UV-induced skin cancers with success. [50][51][52] Epidemiologic evidence suggests that patients taking nonsteroidal anti-inflammatory drugs (NSAIDs) on a regular basis have lower incidence of SCCs. 53 The platelet-activating factor (PAF) and cis-urocanic acid (binding to the receptor 5-HT 2A ) are also mediators of photoimmunosuppression and photocarcinogenesis.…”
Section: Preventionmentioning
confidence: 99%